The Power of the Tribe And Advertisement Avoidance in Online Communities - Kkalis, Myria (2010)
Day by day, social networking sites are becoming more and more popular, making this new kind of online communities primary research objective in the field of e-commerce. Facebook, the biggest social networking site, has more than 500 million active users, with 50% of active users logging on to Facebook in any given day. Recent research on SNS concentrates on the critical issue of advertising avoidance on such sites, and tries to find explanations behind this phenomenon. With the fragmentation of media and increasing clutters, consumers are now exposed to thousands of advertising messages everyday, which not only arrive from traditional media (e.g. television, printed media) but also through World-of Mouth campaigns, online marketing and consumer-generated media (e.g. blogs, online social networking sites). Consequently, consumers have taken matters into their own hands with the aid of technological advances, and have gained control over which ads they will pay attention to, and which content they will avoid if it is of no interest to them. In this study, we will draw from sociology, advertising, consumer behaviour and relationship marketing literature, as well as on key themes such as postmodernism, tribalism, online communities and group behavior. Through the use of qualitative research and in particular semi-structured interviewing, an effort is done to investigate and identify group factors, which have an effect on perceptions of and behavioral response to advertising, and which in turn can facilitate advertisers' ability to form close bonds with members of social networking environments. The findings of the study have considerable managerial and theoretical implications, and can constitute a starting point for further research into this topic.